FRI0410 Factors Associated with Early Damage Accrual in Patients with Systemic Lupus Erythematosus: 12-Month Preliminary Results from the Inception Cohort of the Multicenter Early Lupus Project. (9th June 2015) - Piga, M.; Figus, F.; Mathieu, A.; Prevete, I.; Iuliano, A.; Bettio, S.; Bortoluzzi, A.; Coladonato, L.; Brizzi, G.; Spinelli, F.R.; Tani, C.; Sebastiani, G.D.
Abstract : Background: Preventing organ damage is a major challenge in management of Systemic Lupus Erythematosus (SLE). Few data are available on factors related to development of damage in early stages of the disease. Objectives: To evaluate the early damage accrual and factors determining development and progression of damage in a prospectively followed cohort of SLE patients. Methods: The Early Lupus Project comprises 8 Italian centers recruiting, from the 1st January 2012, an inception cohort of consecutive patients diagnosed with SLE. Patients were enrolled within 12 months of recognition of four or more 1997 ACR classification criteria for SLE. At study entry and then every 6 months a large panel of data was recorded. Here, we report on the development and progression of damage assessed by the SLICC/ACR Damage Index (SDI) at 6-month and 12-month of disease. Using univariate analysis, we assessed the contribution of covariates collected at baseline (demographic, serological, clinical by BILAG2004 domains, disease activity by ECLAM index and health related quality of life by visual analogic scale) in the development of damage (SDI from 0 to ≥1) and increase in pre-existing damage within 12 months from diagnosis. Stepwise regression models were fitted with covariates with p<0.1 to identify factors independently associated with prediction of damage. Results: A total of 161 patients were enrolled in the Early Lupus Project inception cohort up to December 2014; 108 patients (93% Caucasians, 17 males) were eligible for this study having at least 12 months of disease. Mean age at recognition of 4 ACR criteria was 36.3±14.1 years, mean disease duration at recruitment was 2.8±4.3 months (median =1 month; interquartile range 0-3.8). At 6 months of disease, 22 (20.3%) patients had an SDI score of 1 or more (20 patients scored SDI=1; 4 patients scored SDI=2; 3 patients scored SDI≥3). At 12 months of disease, 27 (25.0%) patients had an SDI score of 1 or more and only one patient had increase in pre-existing damage. Age (p=0.01), dyslipidemia (p<0.001), number of active clinical domains according to the BILAG2004 index (p<0.01), active neuropsychiatric (p<0.01) or cardiorespiratory (p=0.02) involvement, familial history of ischemic cardiovascular events (p=0.02) registered at baseline resulted associated with development of damage. Age at diagnosis (p<0.001; OR 1.1 95% CI 1.0-1.3) and active neuropsychiatric involvement (p<0.01; OR 18.7 95% CI 3.1-110.9) were the only independent risk factors for early development of damage in this cohort. No influence of active renal involvement and medications prescribed at baseline was detected in our cohort, likely because they most contribute to development of late-onset damage. Conclusions: Development of organ damage begins early in patients with SLE as effect of modifiable and non-modifiable risk factors. Addressing these since the very early stages of the disease may improve short-term outcome. Disclosure of Interest: None declared